A educação nos aldeamentos indígenas da capitania de São Paulo no século XVIII (entre a expulsão jesuíta e as reformas pombalinas) - Ferreira, Crisney Tritapeppi (2009)
This paper's objective is the study of the education in the XVIII century Capitania de São Paulo gatherings, between the to came jesuits expelling and the pombalinas public instructions reforms. The proof method developed by the historian Carlo Ginburg is the reference to analyse this micro-history. The oraganization of thie study is based on the hgistoric of gatherings creation, indian population ethnic indentification, pombalinas reforms creations and the conflict with the jesuits, that ended up making possilbe the creation of a civil directory to the indian population and the indians education's orientation directed to the work and n ot ot the elementaries studies (read, write and tell)